"Good" and "Bad" Control in Public Administration: The Impact of Performance Evaluation Systems on Employees' Trust in the Employer. (September 2019) - Wiemann, Meike; Meidert, Nadine; Weibel, Antoinette
In the course of the New Public Management reform movement, public administrations have increasingly implemented output-oriented control schemes, including systems to evaluate employees' performance. However, contradictory evidence exists about how such output control that fundamentally differs from traditional bureaucratic control affects performance-relevant employee attitudes and behaviors. In this article, we present evidence that performance evaluations have positive or negative consequences depending on the specific design of the system. Analyzing survey data from 184 employees and 60 supervisors from the German municipal administration by structural equation modeling, we find performance evaluations employed as Management by Objectives (MbO) have a positive impact on trust in the employer and that those designed as Systematic Performance Appraisal (SPA) affect trust negatively. Both relationships are mediated by perceived cooperative climate. These findings advocate employing performance evaluations that are participative, adaptive, learning-oriented, and transparent and thus enable fair cooperation between organizational members.